(untitled) (Jurnal Teknologi (Sciences & Engineering), 2015)
Characterizing a rim enhancing brain lesion remains a challenge and conventional MRI sequences may not be adequate. The aim of our study was to determine whether or not rim enhancing brain lesions of infective origin could be differentiated from neoplasm using MR T2 relaxometry. T2 relaxation times were measured in the central core of 29 rim-enhancing lesions from 23 patients. (10 female, 13 male, age range 12-73 years old). The mean T2 relaxation time of infective lesions was 194.6ms (range 89.5- 498.7ms; SD 144.8) and that of tumour was 893.7 ms (range 147.8-1540.0 ms; SD 431.5). Our early experience showed that T2 relaxometry is a potential quantitative MR technique that can differentiate infective from neoplastic rim enhancing brain lesions.